Analysis of Factors Causing the Non-Implementation of Dance Education in Elementary Schools and Its Impact on Students' Multiple Intelligences - Fatma Nur Rahayu; Deasylina Da Ary (Universitas Negeri Malang, 2025)
Abstract: Dance learning in elementary schools has many obstacles in the application of learning in the classroom. In reality, there are elementary schools that have not implemented dance learning as a subject that is taught, so students do not get the opportunity to develop their knowledge in the field of dance. This study aims to analyze the factors that cause the non-implementation of dance learning in elementary schools and its impact on students' multiple intelligences. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The research instruments used include observation guidelines, interview guidelines, documentation sheets, and field notes. Data validity uses triangulation of sources and techniques, then proceeds with data analysis using the Miles and Huberman model. Data analysis used includes data reduction, data presentation, and conclusion drawing. The results of this study show that the factors that cause the non-implementation of dance learning consist of various aspects, including, among others, teachers, school policies, tight lesson time, and facilities and infrastructure. The impact of this condition is the inhibition of the development of students' multiple intelligences, especially kinesthetic, interpersonal, and intrapersonal intelligence, which should be honed through dance. Abstrak: Pembelajaran tari di sekolah dasar menghadapi banyak hambatan dalam penerapan pembelajaran di kelas. Faktanya, ada sekolah dasar yang belum menerapkan pembelajaran tari sebagai mata pelajaran yang diajarkan, sehingga siswa tidak mendapatkan kesempatan untuk mengembangkan pengetahuan mereka di bidang tari. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang menyebabkan tidak diterapkannya pembelajaran tari di sekolah dasar dan dampaknya terhadap kecerdasan majemuk siswa. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Instrumen penelitian yang digunakan meliputi pedoman observasi, pedoman wawancara, lembar dokumentasi, dan catatan lapangan. Validitas data menggunakan triangulasi sumber dan teknik, kemudian dilanjutkan dengan analisis data menggunakan model Miles dan Huberman. Analisis data yang digunakan meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa faktor-faktor yang menyebabkan tidak dilaksanakannya pembelajaran tari terdiri dari berbagai aspek, antara lain guru, kebijakan sekolah, waktu pelajaran yang ketat, serta fasilitas dan infrastruktur. Dampak dari kondisi ini adalah penghambatan perkembangan kecerdasan majemuk siswa, terutama kecerdasan kinestetik, interpersonal, dan intrapersonal, yang seharusnya dikembangkan melalui tari.